Nickel(II)-catalyzed addition reaction of arylboronic acids to isatins - Zhang, Yu-Yang; Chen, Huixuan; Jiang, Xiaoding; Liang, Hao; He, Xuefeng; Zhang, Yaqi; Chen, Xiangmeng; He, Wenhuan; Li, Yongsu; Qiu, Liqin (Tetrahedron, 2018)
A Ni-catalyzed addition of arylboronic acids to isatins was first developed. The reaction, driven by Ni(acac)2 and dppp as the phosphine ligand, gave 3-aryl-3-hydroxy-2-oxindoles in up to 97% yield. Scopes of benzyl-protected isatins and arylboronic acids were examined. Substituted phenylboronic acids along with fused-ring and heterocyclic boronic acids reacted with isatins smoothly. Preliminary asymmetric catalysis was investigated as well, showing moderate enantioselectivity. The mechanism was also described. A Ni-catalyzed addition of arylboronic acids to isatins was first developed. The reaction, driven by Ni(acac)2 and dppp, gave 3-aryl-3-hydroxy-2-oxindoles in up to 97% yield. Substituted phenylboronic acids along with fused-ring and heterocyclic boronic acids reacted with isatins smoothly. [Display omitted]